Early stages in the entrepreneurship nexus: Business opportunities and individual characteristics - Santos, Susana Helena Correia (2014)
This thesis focuses on the individual-opportunity nexus in the early stages of the entrepreneurship process, and includes five empirical studies. The aim of Study 1 was to contribute to the explanation of cognitive maps during the early stages of entrepreneurship. Results suggest that individuals with greater entrepreneurial experience have richer, clearer and simpler cognitive maps. Study 2 sought to obtain evidence concerning the basic dimensions included in cognitive prototypes pertaining to opportunity recognition and decision to launch a new venture. For the “business opportunity” prototype these are utility and distinctiveness while for the decision to launch a new venture, the basic dimensions are feasibility and motivational aspects. The two studies mentioned above focused on the opportunity side of the nexus. For the individual side of the nexus, we focused on the entrepreneurial potential construct applied in different contexts. With Study 3, we put forward a theoretical model for the entrepreneurial potential construct. Through six research steps, this study presented the development of the Entrepreneurial Potential Assessment Inventory, which can be used to measure the entrepreneurial potential construct. Study 4 aimed to analyse the predictive capacity of entrepreneurial potential profiling among entrepreneurial team members. Our results showed that, in a venture competition context, the teams with higher results in socio-psychological aspects became finalists. Study 5 presented a methodology for the selection of potential entrepreneurs for an entrepreneurship promotion program. The main results showed that individual and business opportunity characteristics are critical dimensions. Based on these empirical studies, this thesis also describes valuable tools that can contribute towards fostering entrepreneurship in Portugal.